A Simply Synthesized, Tough Polyarylene with Transient Mechanochromic Response. (24th November 2017) - Kempe, Fabian; Brügner, Oliver; Buchheit, Hannah; Momm, Sarah N.; Riehle, Felix; Hameury, Sophie; Walter, Michael; Sommer, Michael
Abstract: A simple and high‐yielding route to tough polyarylenes of the type poly( meta, meta, para ‐phenylene) (P mmp P) is developed. P mmp P is tough even in its as‐synthesized state which has an intermediate molar mass of M w ≈60 kg mol −1 and exhibits outstanding mechanical properties at further optimized molecular weight of M w =96 kg mol −1, E= 0.9 GPa, ϵ= 300 %. Statistical copolymers with para, para ‐spiropyran (SP) are mechanochromic, and the toughness allows mechanochromism to be investigated. Strained samples instantaneously lose color upon force release. DFT calculations show this phenomenon to be caused by the P mmp P matrix that allows build‐up of sufficiently large forces to be transduced to SP, and the relatively unstable corresponding merocyanine (MC) form arising from the aromatic co‐monomer. MC units covalently incorporated into P mmp P show a drastically reduced half life time of 3.1 s compared to 4.5 h obtained for SP derivatives with common 6‐nitro substitution.